Nitrogen-doped carbon-loaded Pt / Ca bimetallic atom electrocatalyst as well as preparation method and application thereof
By using nitrogen-doped carbon-supported Pt/Ca bimetallic electrocatalyst in an alkaline environment, the existing electrocatalysts have been solved, and the existing electrocatalysts have insufficient oxygen reduction reaction activity and high cost in an alkaline environment are achieved, and a highly efficient, stable and low-cost catalytic effect is achieved.
Patent Information
- Application Number
- CN202411983105.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing electrocatalysts have insufficient oxygen reduction reaction activity in alkaline environments and are costly, making it difficult to meet the high-efficiency and low-cost catalytic needs.
A nitrogen-doped carbon-supported Pt/Ca bimetallic atomic electrocatalyst is used. This catalyst significantly improves the electrocatalytic redox reaction activity in an alkaline environment through the active sites constructed by bimetals and the efficient atomic utilization rate.
The oxygen reduction reaction activity is significantly improved in an alkaline environment, excellent stability and low cost, and the problems of insufficient activity and high cost in the prior art are overcome.
Smart Images

Figure CN119800425A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalyst preparation, and in particular to a nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst and a preparation method and application thereof. Background Art
[0002] Electrocatalytic reaction is a method that uses an external electric potential to promote chemical reactions. It is green and efficient and can be used in the fields of catalytic organic synthesis, electrolysis of water to produce hydrogen, electrochemical energy storage, etc. The principle of electrocatalytic reaction is to introduce electrons, cations or anions by applying an external electric field, thereby changing the thermodynamic and kinetic processes of the reaction, accelerating the reaction rate and improving the reaction selectivity. Electrocatalytic reaction technology has broad application prospects in the fields of environmental protection and energy. Especially in the field of new energy, electrocatalytic reaction technology has become an important means to prepare efficient, clean and sustainable energy. The research on electrocatalytic reaction involves the fields of chemistry, physics, biology and other interdisciplinary fields, and new electrocatalytic reaction systems and new electrocatalysts are constantly emerging.
[0003] Diatom catalysts can be effectively connected by exploiting various interactions between two metal atoms. Compared with single-atom catalysts, diatomic catalysts have the advantages of larger atomic loading, interaction between diatomic sites, and wider catalytic applications. The most prominent among them are the interactions between diatomic sites: synergistic effect, distance enhancement effect, and electronic effect. The interaction between diatomic sites is not only a simple superposition of individual atomic functions, but also helps to regulate the electronic structure of catalytic active sites, effectively improving the catalytic performance of multiple advanced applications. Since the concept of single-atom catalysts (SACs) was proposed in 2011, the controllable design of SACs, including coordination and electronic structure, has been fully developed. Due to the small contact area of SACs and the relatively weak interaction between atoms and supports, it provides the necessary space and possibility for the development of high-performance diatomic catalysts (DACs) with synergistic electronic enhancement effects, which have broad application prospects in multiple fields such as thermal catalysis, photocatalysis, and electrocatalysis. Summary of the invention
[0004] In view of this, the present application provides a nitrogen-doped carbon-loaded Pt / Ca bimetallic atomic electrocatalyst, a preparation method and application thereof. The nitrogen-doped carbon-loaded Pt / Ca bimetallic atomic electrocatalyst has excellent performance, good stability and low cost. Through the active sites constructed by bimetals and nearly 100% atomic utilization, the activity of the electrocatalytic oxygen reduction reaction in an alkaline environment is significantly improved, and the defects of the above-mentioned prior art can be effectively overcome.
[0005] The first aspect of the present application provides a method for preparing a nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst, comprising the following steps:
[0006] S1. Dissolve dimethylimidazole in methanol I, disperse by ultrasonic, and mark it as solution A; dissolve zinc salt, platinum salt and calcium salt in methanol II, disperse by ultrasonic, and mark it as solution B; pour solution B into solution A, and stir vigorously to form a uniform dispersed solution;
[0007] S2, subjecting the uniformly dispersed solution to a hydrothermal reaction, and cooling the solution to room temperature naturally after the reaction is completed, and subjecting the product to centrifugation, washing, and vacuum drying to obtain a Pt-Ca-ZIF8 precursor;
[0008] S3. Grind the Pt-Ca-ZIF8 precursor into granules, add sodium chloride powder, perform high-temperature pyrolysis under a protective atmosphere, dissolve the pyrolyzed powder in deionized water, stir, wash, filter, and vacuum dry to obtain a nitrogen-doped carbon-loaded Pt / Ca bimetallic atom electrocatalyst.
[0009] Preferably, in step S2, the temperature of the hydrothermal reaction is 120-130° C., and the time of the hydrothermal reaction is 5-6 hours.
[0010] Preferably, in step S2, the specific process of washing is: firstly washing the precipitate after centrifugation with a dimethylformamide solution until the supernatant is colorless; and then washing with anhydrous methanol for 3 times.
[0011] Preferably, in step S2, the vacuum drying temperature is 60-65° C., and the vacuum drying time is 8-10 h.
[0012] Preferably, in step S3, the specific process of high temperature pyrolysis is: placing in a tube furnace under argon protection at a rate of 5°C / min to 900-1000°C, the pyrolysis time is 2h. Preferably, the temperature is raised to 900°C.
[0013] Preferably, in step S3, the mass ratio of the sodium chloride powder to the Pt-Ca-ZIF8 precursor is 1:1; or
[0014] The ratio of the pyrolyzed powder to deionized water is (10 mg to 100 mg): (100 to 1000 ml) or
[0015] The stirring washing time is 1 to 2 hours; the vacuum drying temperature is 60 to 65° C., and the drying time is 5 to 6 hours.
[0016] Preferably, in step S1, the ultrasonic dispersion time of solution A and solution B is 10 to 15 minutes; and the vigorous stirring time of the uniformly dispersed solution is 1 to 2 hours.
[0017] Preferably, in step S1, the ratio of dimethylimidazole, zinc salt, platinum salt and calcium salt is 16mmol:4mmol:0.2mmol:0.1mmol; or
[0018] The zinc salt is zinc nitrate hexahydrate, the platinum salt is platinum acetylacetonate, and the calcium salt is calcium chloride; or
[0019] The concentration of dimethylimidazole in methanol I is 1.6-2 mm, the concentration of the mixture of zinc salt, platinum salt and calcium salt in methanol II is 0.15-0.2 mm, and the usage ratio of methanol I to methanol II is 10 ml:30 ml.
[0020] The second aspect of the present application also provides a nitrogen-doped carbon-loaded Pt / Ca atomic electrocatalyst, which is a nitrogen-doped carbon-loaded Pt / Ca atomic electrocatalyst prepared by the above method.
[0021] The third aspect of the present application also provides the use of the above-mentioned nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst in the redox reaction of alkaline electrolyte.
[0022] Compared with the prior art, this application has the following beneficial effects:
[0023] (1) The present application systematically controls the synthesis temperature, adds sodium chloride powder and other process parameters to prepare a bimetallic atomic structure of platinum single atom and calcium single atom on a nitrogen-doped carbon substrate, the general formula of which is Pt-Ca-NC, wherein NC is a nitrogen-doped carbon substrate material, wherein the Pt metal atom and the Ca metal atom are anchored on the carbon substrate by nitrogen.
[0024] (2) Compared with other platinum-based bimetallic atom catalysts, the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst in the present application introduces calcium, one of the alkaline earth metal elements, into the Pt-Ca-NC synthesized in the present application for heterogeneous catalysis, thereby reducing the price cost while maintaining excellent performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 The morphology and coordination environment characterization diagram of the Pt-Ca-NC catalyst prepared in Example 1 of the present application; Figure 1 (a) is a TEM image; Figure 1 (b) is the HAADF-STEM image. Figure 1 (c) is the XRD pattern;
[0027] Figure 2 This is a STEM-EDX image of Pt-Ca-NC prepared in Example 1 of the present application;
[0028] Figure 3 ORR-LSV curves of Pt-Ca-NC prepared in Example 1 of the present application, Pt-NC, Ca-NC, NC prepared in Comparative Examples 1-3, and commercial Pt / C in 0.1 M KOH;
[0029] Figure 4 Current-time stability test of Pt-Ca-NC prepared in Example 1 of the present application, Pt-NC, Ca-NC prepared in Comparative Examples 1-2, and commercial Pt / C at a rotating disk speed of 1600 rpm;
[0030] Figure 5 The current-time stability test of the Pt-Ca-NC prepared in Example 1 of the present application at zero rotation speed of the rotating disk;
[0031] Figure 6 The durable cycle stability test of Pt-Ca-NC prepared in Example 1 of the present application;
[0032] Figure 7 ORR-LSV curves of Pt-Ca-NC prepared in Example 1 of the present application, Pt-Ca-NC-2 prepared in Example 2, and Pt-Ca-NC-3 prepared in Example 3 in 0.1 M KOH. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0034] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0035] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0036] Example 1
[0037] The preparation method of the Pt-Ca-NC catalyst of this embodiment comprises the following steps:
[0038] Dissolve 16mmol of 2-methylimidazole in 10ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution A; dissolve 4mmol of Zn(NO3)2*6H2O, 0.2mmol of Pt(acac)2, and 0.1mmol of CaCl2 in 30ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution B. Pour solution B into solution A, stir vigorously for 1h, move to a hydrothermal kettle, and hydrothermal in an oven at 120° for 5h. After it naturally cools to room temperature, centrifuge the product, wash the precipitate after centrifugation with DMF solution until the supernatant is colorless, and then wash it with anhydrous methanol for 3 times. Transfer the washed sample to a vacuum drying oven and dry it at 60°C for 10h to obtain the Pt-Ca-ZIF8 precursor. The Pt-Ca-ZIF8 precursor sample was ground into fine particles, and the sample was collected and transferred to a tube furnace. NaCl powder was weighed in a 1:1 ratio with the sample weight and placed in the tube furnace. It was heated to 900°C at a heating rate of 5°C / min under Ar atmosphere and maintained for 2 hours for thermal decomposition. Then it was naturally cooled to room temperature. The sample was taken out and moved to a beaker. 100 ml of deionized water was added. The powder was heated to 60°C and stirred for 2 hours. Then the solution was filtered. During the filtration process, 1 L of deionized water was added for washing. Then the filtered sample was transferred to a vacuum drying oven and dried at 60°C for 5 hours to obtain a nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst, which was recorded as Pt-Ca-NC catalyst.
[0039] like Figure 1 As shown in (a), there is no aggregation of platinum metal and calcium metal nanoparticles on the catalyst surface; Figure 1 As shown in (b), it can be seen that platinum metal and calcium metal are distributed in atomic size on the nitrogen-doped carbon substrate. Figure 1 As shown in (c), two peaks appear in the XRD pattern of the Pt-Ca-NC catalyst at around 26.5° and 42.8°, corresponding to the (002) and (100) crystal planes of carbon, respectively. The absence of diffraction peaks of platinum metal, calcium metal and their oxides indicates that platinum and calcium exist in the form of single atom coexistence, which is consistent with the results of TEM and HAADF-STEM images.
[0040] Figure 2 The figure shows the element energy spectrum of STEM-EDX. As shown in the figure, there are obvious distributions of platinum and calcium elements on the nitrogen-doped carbon substrate, which confirms that single platinum atoms and single calcium atoms are successfully loaded on the nitrogen-doped carbon substrate.
[0041] It can be seen that in the Pt-Ca-NC catalyst prepared in this example, the platinum single atom and the calcium single atom are anchored on the carbon substrate through nitrogen and show strong electronic interaction.
[0042] Example 2
[0043] The preparation method of the Pt-Ca-NC-2 catalyst provided in this embodiment can refer to Example 1, except that the high-temperature pyrolysis temperatures of the two are different. In Example 2, heating is performed to 950°C at a heating rate of 5°C / min under Ar atmosphere as a variable.
[0044] Example 3
[0045] The Pt-Ca-NC-3 provided in this embodiment can refer to Example 1, except that the high-temperature pyrolysis temperatures of the two are different. Example 3 is heated to 1000°C at a heating rate of 5°C / min in an Ar atmosphere as a variable.
[0046] Comparative Example 1
[0047] In this comparative example, the platinum metal atom forms an isolated single atomic site, and the general formula is Pt-NC. The preparation method of the Pt-NC catalyst in this comparative example comprises the following steps:
[0048] Dissolve 16mmol of 2-methylimidazole in 10ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution A; dissolve 4mmol of Zn(NO3)2*6H2O and 0.2mmol of Pt(acac)2 in 30ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution B. Pour solution B into solution A, stir vigorously for 1h, move to a hydrothermal kettle, hydrothermal in an oven at 120° for 5h, and wait until it naturally cools to room temperature. Centrifuge it, wash the precipitate after centrifugation with DMF solution until the supernatant is colorless, and then wash it with anhydrous methanol 3 times. Transfer the washed sample to a vacuum drying oven and dry it at 60°C for 10h to obtain the Pt-ZIF8 precursor. The Pt-ZIF8 precursor sample was ground into fine particles, and the sample was collected and transferred to a tube furnace. NaCl was weighed in a 1:1 ratio with the sample weight and placed in the tube furnace. It was heated to 900°C at a heating rate of 5°C / min under Ar atmosphere and maintained for 2 hours for thermal decomposition. Then it was naturally cooled to room temperature. The sample was taken out and moved to a beaker. 100 ml of deionized water was added. The powder was stirred at 60°C for 2 hours, and then the solution was filtered. During the filtration process, 1 L of deionized water was added for washing. Then the filtered sample was transferred to a vacuum drying oven and dried at 60°C for 5 hours to obtain a Pt-NC catalyst.
[0049] Comparative Example 2
[0050] In this comparative example, the calcium metal atom forms an isolated single atomic site with the general formula of Ca-NC. The preparation method of the Ca-NC catalyst in this comparative example comprises the following steps:
[0051] Dissolve 16mmol of 2-methylimidazole in 10ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution A; dissolve 4mmol of Zn(NO3)2*6H2O and 0.1mmol of CaCl2 in 30ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution B. Pour solution B into solution A, stir vigorously for 1h, move to a hydrothermal kettle, hydrothermal in an oven at 120° for 5h, and wait until it naturally cools to room temperature. Centrifuge the product, wash the precipitate after centrifugation with DMF solution until the supernatant is colorless, and then wash it with anhydrous methanol for 3 times. Transfer the washed sample to a vacuum drying oven and dry it at 60°C for 10h to obtain the Ca-ZIF8 precursor. The Ca-ZIF8 precursor sample was ground into fine particles, and the sample was collected and transferred to a tube furnace. NaCl was weighed in a 1:1 ratio with the sample weight and placed in the tube furnace. It was heated to 900°C at a heating rate of 5°C / min under Ar atmosphere and maintained for 2 hours for thermal decomposition. Then it was naturally cooled to room temperature. The sample was taken out and moved to a beaker. 100 ml of deionized water was added. The powder was stirred at 60°C for 2 hours, and then the solution was filtered. During the filtration process, 1 L of deionized water was added for washing. Then the filtered sample was transferred to a vacuum drying oven and dried at 60°C for 5 hours to obtain a Ca-NC catalyst.
[0052] Comparative Example 3
[0053] In this comparative example, a nitrogen-doped carbon substrate material is prepared, and the general formula is NC. The preparation method of the NC catalyst in this comparative example comprises the following steps:
[0054] Dissolve 16mmol of 2-methylimidazole in 10ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution A; dissolve 4mmol of Zn(NO3)2*6H2O in 30ml of methanol, dissolve by ultrasonic dispersion for 10min, and mark it as solution B. Pour solution B into solution A, stir vigorously for 1h, move to a hydrothermal kettle, hydrothermal in an oven at 120° for 5h, and wait until it naturally cools to room temperature. Centrifuge the product, wash the precipitate after centrifugation with DMF solution until the supernatant is colorless, and then wash it with anhydrous methanol 3 times. Transfer the washed sample to a vacuum drying oven and dry it at 60°C for 10h to obtain the ZIF8 precursor. The ZIF8 precursor sample was ground into fine particles, and the sample was collected and transferred to a tube furnace. NaCl was weighed in a 1:1 ratio with the sample weight and placed in the tube furnace. It was heated to 900°C at a heating rate of 5°C / min under Ar atmosphere and maintained for 2 hours for thermal decomposition. Then it was naturally cooled to room temperature. The sample was taken out and moved to a beaker. 100 ml of deionized water was added. The powder was stirred at 60°C for 2 hours, and then the solution was filtered. During the filtration process, 1 L of deionized water was added for washing. Then the filtered sample was transferred to a vacuum drying oven and dried at 60°C for 5 hours to obtain an NC catalyst.
[0055] Test Case
[0056] The Pt-Ca-NC, Pt-NC, Ca-NC and NC catalysts prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were tested for oxygen reduction activity in an alkaline electrolyte: a rotating disk electrode device was used, a carbon rod was used as a counter electrode, an Ag / AgCl electrode was used as a reference electrode, a glassy carbon electrode was used as a counter electrode, and the alkaline electrolyte was 0.1M KOH. 5 mg of the target sample was dissolved in a solvent containing 25 microliters of nafion, 50 microliters of ultrapure water and 425 microliters of isopropanol, 10 microliters of electrode ink was dripped onto the glassy carbon electrode, dried naturally, and electrochemical testing was performed at a rotation speed of 1600 rpm.
[0057] The obtained oxygen reduction LSV curve is as follows Figure 3 As shown in the figure, it can be seen that Pt-Ca-NC exhibits the highest oxygen reduction starting potential (1.00V) and half-wave potential (0.88V), which is better than Pt-NC prepared in Comparative Example 1 (0.97V and 0.86V), Ca-NC prepared in Comparative Example 2 (0.96V and 0.79V), NC prepared in Comparative Example 3 (0.91V and 0.75V) and commercial Pt / C (0.99V and 0.84V). It can be seen that the Pt-Ca-NC catalyst prepared in this application has a better oxygen reduction electrocatalytic activity under 0.1M KOH conditions.
[0058] The Pt-Ca-NC prepared in Example 1 was subjected to a stability test in 0.1 M KOH. Figure 4 As shown in the figure, when the potential of the catalyst was 0.77 V, the current density remained at 98.74% after two hours, which was better than the Pt-NC prepared in Comparative Example 1 (95.84%), the Ca-NC prepared in Comparative Example 2 (94.16%) and the commercial Pt / C (89.98%). Figure 5 As shown in Figure 2, the Pt-Ca-NC catalyst has no obvious up and down fluctuations within 120 hours under the constant voltage test of 0.76 V (vs. RHE) with no rotating disk speed. Figure 6 As shown, after 10,000 cyclic voltammetry tests, the half-wave potential decayed by only 5 mV, indicating that the Pt-Ca-NC catalyst prepared in Example 1 exhibited excellent oxygen reduction electrocatalytic stability in 0.1 M KOH.
[0059] like Figure 7 As shown, by regulating the high-temperature pyrolysis temperature as a process parameter, the half-wave potential of the Pt-Ca-NC catalyst obtained by pyrolysis at 900°C is 0.88V, which has better oxygen reduction electrocatalytic activity than the Pt-Ca-NC-2 obtained by pyrolysis at 950°C in Example 2 (half-wave potential of 0.83V) and the Pt-Ca-NC-3 obtained by pyrolysis at 1000°C in Example 3 (half-wave potential of 0.79V), and 900°C is determined to be the optimal temperature for synthesis.
[0060] In summary, in the alkaline oxygen reduction process of the Pt-Ca-NC prepared in Example 1 of the present application, the interactions between the prominent diatomic sites of the platinum-calcium diatomic catalyst: synergistic effect, distance enhancement effect and electronic effect make the Pt-Ca-NC catalyst prepared in Example 1 have excellent activity and stability in the alkaline oxygen electroreduction process.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst, characterized in that: The following steps are involved: S1, dissolve dimethylimidazole in methanol Ⅰ, disperse by ultrasonic, and mark it as solution A; Dissolve zinc salt, platinum salt and calcium salt in methanol II, disperse by ultrasonic, and mark as solution B; pour solution B into solution A, and stir vigorously to form a uniform dispersed solution; S2, subjecting the uniformly dispersed solution to a hydrothermal reaction, and cooling the solution to room temperature after the reaction is completed, and subjecting the product to centrifugation, washing, and vacuum drying to obtain a Pt-Ca-ZIF8 precursor; S3. Grind the Pt-Ca-ZIF8 precursor into granules, add sodium chloride powder, perform high-temperature pyrolysis under a protective atmosphere, dissolve the pyrolyzed powder in deionized water, stir, wash, filter, and vacuum dry to obtain a nitrogen-doped carbon-loaded Pt / Ca bimetallic atom electrocatalyst.
2. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 120-130° C., and the time of the hydrothermal reaction is 5-6 hours.
3. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S2, the specific process of washing is: firstly washing the precipitate after centrifugation with a dimethylformamide solution until the supernatant is colorless; and then washing with anhydrous methanol for 3 times.
4. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S2, the vacuum drying temperature is 60-65°C, and the vacuum drying time is 8-10 hours.
5. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S3, the specific process of high-temperature pyrolysis is: placing in a tubular furnace under argon protection at a rate of 5°C / min to 900-1000°C, and the pyrolysis time is 2h.
6. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S3, the mass ratio of sodium chloride to Pt-Ca-ZIF8 precursor is 1:1; or The ratio of the pyrolyzed powder to deionized water is (10-100 mg): (100-1000 ml); or The stirring washing time is 1 to 2 hours; the vacuum drying temperature is 60 to 65° C., and the drying time is 5 to 6 hours.
7. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S1, the ultrasonic dispersion time of solution A and solution B is 10 to 15 minutes; the vigorous stirring time of the uniformly dispersed solution is 1 to 2 hours.
8. The method for preparing the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 1, characterized in that: In step S1, the ratio of dimethylimidazole, zinc salt, platinum salt and calcium salt is 16mmol:4mmol:0.2mmol:0.1mmol; or The zinc salt is zinc nitrate hexahydrate, the platinum salt is platinum acetylacetonate, and the calcium salt is calcium chloride; or The concentration of dimethylimidazole in methanol I is 1.6-2 mm, the concentration of the mixture of zinc salt, platinum salt and calcium salt in methanol II is 0.15-0.2 mm, and the usage ratio of methanol I to methanol II is 10 ml:30 ml.
9. A nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst, characterized in that: A nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst prepared by the method described in any one of claims 1 to 8.
10. Use of the nitrogen-doped carbon-supported Pt / Ca bimetallic atom electrocatalyst according to claim 9 in redox reactions in alkaline electrolytes.
Citation Information
Patent Citations
Method for preparing cobalt-isolated platinum nanoparticle catalyst by two-step annealing method and application of cobalt-isolated platinum nanoparticle catalyst
CN116581316A
Preparation method and application of transition metal / nitrogen co-doped porous carbon bifunctional electrocatalyst
CN118073583A
Method and apparatus for determining a degree of dementia of a user
KR102274072B1